Spatiotemporal variation in water quality and identification and quantification of areas sensitive to water quality in Hulun lake, China - Wu, Rong; Zhang, Sheng; Liu, Yu; Shi, Xiaohong; Zhao, Shengnan; Kang, Xueer; Quan, Dong; Sun, Biao; Arvola, Lauri; Li, Guohua (Ecological indicators, 2023)
[Display omitted] •The WQI with improved weighting was applied to assess changes to the water quality of Hulun Lake.•The OLS model identified factors influencing lake chlorophyll a.•The northwest shore was identified as a major input of pollutants. This study aimed at characterizing the spatiotemporal variability in water quality in Hulun Lake. In an attempt to assess the water quality status of the lake, data acquired from 13 monitoring points in Hulun Lake from 2012 to 2020 was applied to the improved composite water quality identification index (WQI). The ordinary least squares (OLS) model was used to identify areas of the lake vulnerable to water pollution. The results showed an increase in the WQI value of Hulun Lake and the water quality deteriorated during 2012–2016. The water quality began to improve gradually in 2017. The main variable affecting water quality in the lake transitioned from chemical oxygen demand (CODcr) and total nitrogen (TN) to CODcr and total phosphorus(TP). This shift in major pollutants was an important factor contributing to deterioration in water quality. Seasonal differences in water quality may be attributed to migration of pollutants [CODcr, total dissolved solids (TDS)] to the subglacial water column during the ice-covered period and the subsequent blocking effect of the ice cap. A spatially based OLS model identified the critical impact of Chl.a on water quality. Water transfers were identified as a major factor contributing to an improvement in water quality and to pollutant transformation and contributed to increase in the water quality sensitive area. Despite recent efforts to improve the water quality of Hulun Lake, input of exogenous pollutants, increase in endogenous pollutants, as well as the anaerobic conditions of the ice layer pose significant challenges to the management of Hulun Lake. The implementation of pollutant control measures are, in particular, recommended on the northwest shore for managing the water quality of the lake.